The roles of interpersonal trust on relationship between social factors and knowledge sharing behaviour - Norfadzilah, Abdul Razak (2021)
The service sector is an industry that deals with knowledge and expertise. In general, knowledge is valuable and difficult to imitate. For service organizations, sustaining knowledge is vital for competitive advantage. The absence of knowledge sharing behaviour among employees is damaging to businesses in the form of cost incurred due to extra effort on human talent development and acquisition activities in order to increase productivity. Thus, it is important to further examine the factors that influence knowledge sharing behaviour. Applying the Relational Model Theory (RMT), several social factors (i.e., social cohesion, legitimate power, coercive power, referent power, expert power, affective commitment, intrinsic and extrinsic reward) have been identified to predict employee’s knowledge sharing behaviour. In addition, the role of interpersonal trust as a mediator on the relationship between social factors and knowledge sharing behaviour was also tested. 203 skilled workers from the service sector were selected as respondents to answer the questionnaires which contains measures of the studied variables. Statistical analysis was performed using Partial Least Square (PLS) software. The findings revealed that social cohesion, affective commitment, intrinsic reward and interpersonal trust have direct relationships with knowledge sharing behaviour. However, interpersonal trust only mediates the relationship between expert power, affective commitment, extrinsic and intrinsic rewards, and knowledge sharing behaviour. The finding implies the importance of relational context in increasing interpersonal trust for enhancing knowledge sharing behaviour among employees. Therefore, organizations should focus on developing strategies that would increase social cohesion, expert power, and affective commitment among their employees. In addition, organizations should also revise its rewards system so that it is directed at increasing interpersonal trust among the employees. All of these are important for increased knowledge sharing behaviour.